Epidemiology of Leprosy in Indonesia: a Retrospective Study - Lubis, Ramona Sari; Anum, Qaira; Argentina, Fifa; Menaldi, Sri Linuwih; Gunawan, Hendra; Yuniati, Renni; Mulianto, Nur Rachmat; Siswati, Agnes Sri; Widasmara, Dhelya; Rusyati, Luh Made Mas; Mamuaja, Enricco Hendra; Muchtar, Vitayani; Cita Rosita Sigit Prakoeswa; Agusni, Regitta Indira; Bagus Haryo Kusumaputra; Medhi Denisa Alinda; Listiawan, Muhammad Yulianto (Faculty of Medicine, Universitas Airlangga, 2022)
Background: According to WHO data, the number of new cases of leprosy has decreased in 2019. However, Indonesia continues to provide a significant number of cases. According to statistics, India, Brazil, and Indonesia account for 79 percent of all instances. Purpose: This study aims to describe the profile of leprosy patients, and involves all Dermatology and Venereology Academic Hospitals in Indonesia. Methods: This study was a retrospective study of 2461 patients from Dermatology and Venereology Outpatient Clinic at 13 Academic Hospitals in Indonesia between January 2018 and December 2020. Result: Subjects in this study were dominated by males (66.8%) and aged > 14 years (95.3%). The most common type of leprosy was multibacillary (MB) (86.2%), and erythema nodosum leprosum (ENL) was the most leprosy reaction (20.3%). Majority of the subjects experienced disability in the hands (26.6%), in grade 1. Conclusion: Leprosy cases in Indonesia are mostly experienced by adult males. The most common type of leprosy is MB, with ENL being the most common leprosy reaction. Grade 1 disability is the most prevalent, therefore proper education is necessary to keep patients from progressing to grade 2 disability.